The Use of Common Ground as a Politeness Strategy among Traders of Tudun Wada Super Store, Gusau Local Government Area in Zamfara State, Nigeria (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Speech acts and gestures reflect a transaction process interaction between sellers and buyers. Speech events in traditional markets can cause inconveniences such as the expression of anger, pressure, anxiety, or an insult, which can occur during the bargaining process. It is against this background that this study examines how traders in Super Stores of Tudun Wada in Gusau metropolis use common grounds as politeness strategies for business purposes.  The theoretical framework of this study is Politeness Theory developed by Penelope Brown and Stephen Levinson while the methodology adopted is both qualitative and descriptive research. The research data come from traders of Tudun Wada Super Store in Gusau. The data were gathered through observation method which required skilled recording techniques. The researchers transcribed the recorded audio and classified it according to the data card. Matching method was used for data analysis, in which the researchers relate the data to the context of the utterance event. The researchers used Miles and Huberman's (2009) stages of qualitative analysis to analyze the data. The finding of this study reveals that the socio-cognitive approach eliminates the conflicts between the pragmatic and cognitive approaches to common ground by integrating them into a holistic picture that offers an emergence-through-use view of common ground.The study, therefore, concludes that communication is an intentional action that is usually attended by adequate and sufficient resources on the basis of common socio-cultural background with the aid of common ground.
Keywords: Politeness; Communication; Language; Politeness Strategy; Common Ground